2019
DOI: 10.3390/polym11010151
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement Effect and Mechanism of Longitudinal Ultrasonic Vibration on the Injection Molding Quality of a Polymeric Micro-Needle Array

Abstract: A polymeric micro-needle array with high quality has been fabricated using a longitudinal ultrasonic-assisted micro-injection molding (LUμIM) method. To realize the practicability and stability in actual industrial processing, this paper is aimed at studying the improvement mechanism of ultrasonic vibration on the molding quality. The melt-filling process in the micro-needle array cavity is simulated, and the improvement effect of ultrasonic vibration is discussed. The enhancement effect of ultrasonic vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ultrasonic processing technology, as a novel molding processing technology, has been widely used in recent years for the injection molding, extrusion molding, and compression molding of polymers [9,10]. Despite different ways of applying ultrasonic energy, studies have found that ultrasounds can affect the microstructure filling performance [11], change the material properties [12], affect the extrusion swelling [13], improve the weld line strength of the plastic parts [14], and reduce the interface friction during ejection [15]. However, current studies are mainly based on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic processing technology, as a novel molding processing technology, has been widely used in recent years for the injection molding, extrusion molding, and compression molding of polymers [9,10]. Despite different ways of applying ultrasonic energy, studies have found that ultrasounds can affect the microstructure filling performance [11], change the material properties [12], affect the extrusion swelling [13], improve the weld line strength of the plastic parts [14], and reduce the interface friction during ejection [15]. However, current studies are mainly based on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The results were that the filling area of the plastic parts was improved by about 6.91% and symmetric deviation was improved 15.62% on average because of ultrasonic vibration. Lateral experiment and simulation proved it again [ 49 , 59 ]. The improvement of the mass or the filling length of molded parts is related to the temperature change under the action of ultrasonic vibration field.…”
Section: Ultrasound-assisted Micro-injection Moldingmentioning
confidence: 96%
“…At present, the theory on the effect of vibration on the interior and surface of plastically worked materials is based on two fundamental effects [ 23 , 24 ]. That is, the volume effect that affects the mechanical properties and the surface effect that affects the sliding friction.…”
Section: Introductionmentioning
confidence: 99%